Proceedings of the 2013 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining 2013
DOI: 10.1145/2492517.2492583
|View full text |Cite
|
Sign up to set email alerts
|

Location-specific tweet detection and topic summarization in Twitter

Abstract: Automatic detection of tweets that provide Location-specific information will be extremely useful in conveying geo-location based knowledge to the users. However, there is a significant challenge in retrieving such tweets due to the sparsity of geo-tag information, the short textual nature of tweets, and the lack of pre-defined set of topics. In this paper, we develop a novel framework to identify and summarize tweets that are specific to a location. First, we propose a weighting scheme called Location Centric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…One is that content might change over time, and therefore new tweets might discuss new topics that the classifiers have not seen before. Another caveat is that the content of the tweet might not be location-specific; in a previous study, Rakesh et al [45] found that the content of only 289 out of 10,000 tweets was location-specific. Figure 2 shows an example of a tweet and the eight features listed above.…”
Section: )mentioning
confidence: 99%
“…One is that content might change over time, and therefore new tweets might discuss new topics that the classifiers have not seen before. Another caveat is that the content of the tweet might not be location-specific; in a previous study, Rakesh et al [45] found that the content of only 289 out of 10,000 tweets was location-specific. Figure 2 shows an example of a tweet and the eight features listed above.…”
Section: )mentioning
confidence: 99%
“…The technique proposed by Rakesh, Reddy, Singh, and Ramachandran () generates a summary of tweets that are specific to a location. Specifically, it leverages on the tweets content and the network information of users to identify location‐specific tweets.…”
Section: Related Workmentioning
confidence: 99%
“…Bigram sequences are the different combination of keywords, numbers, hashtags used by users while tweeting. [8] Twitter data is known for its diverse uses, it is also used to predict real time events. One such model is Temporal model, which describes the time series of data.…”
Section: Related Workmentioning
confidence: 99%